Fracture loads of screw-retained implant-supported zirconia prostheses after thermal and mechanical stress. Issue 3 (July 2020) - Honda, Junichi; Komine, Futoshi; Kusaba, Kosuke; Kitani, Jin; Matsushima, Keisuke; Matsumura, Hideo
Abstract: Purpose: The objective of the present study was to evaluate fracture loads of screw-retained implant-supported zirconia prostheses after artificial aging. Methods: Four types of screw-retained implant-supported prostheses were fabricated ( n = 11 each); porcelain-veneered zirconia prosthesis (PVZ), indirect composite-veneered zirconia prosthesis (IVZ), porcelain-fused-to-metal prosthesis (PFM), and monolithic zirconia prosthesis (ML). The specimens were subjected to 10, 000 thermocycles and cyclic loading for 1.2 million cycles. Fracture loads were measured, and the data were analyzed with the Kruskal–Wallis and Steel–Dwass tests ( α = 0.05). Results: All specimens survived the artificial aging procedures. The fracture loads for the PVZ (1.52 kN), IVZ (1.62 kN), and PFM groups (1.53 kN) did not significantly differ; however, the fracture load for the ML group (6.61 kN) was significantly higher than those for the other groups. The fracture load for the IVZ group was comparable to those for the PVZ and PFM groups. Conclusions: The monolithic zirconia prostheses exhibited significantly higher fracture loads than the bilayered prostheses. All the investigated types of screw-retained implant-supported zirconia prostheses appear sufficient to resist posterior masticatory forces during long-term clinical use.